2022
DOI: 10.7150/ijbs.67770
|View full text |Cite
|
Sign up to set email alerts
|

HPV E6/E7 promotes aerobic glycolysis in cervical cancer by regulating IGF2BP2 to stabilize m6A-MYC expression

Abstract: Enhanced aerobic glycolysis constitutes an additional source of energy for tumor proliferation and metastasis. Human papillomavirus (HPV) infection is the main cause of cervical cancer (CC); however, the associated molecular mechanisms remain poorly defined, as does the relationship between CC and aerobic glycolysis. To investigate whether HPV 16/18 E6/E7 can enhance aerobic glycolysis in CC, E6/E7 expression was knocked down in SiHa and HeLa cells using small interfering RNA (siRNA). Then, glucose uptake, lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…IGF2BP2 also promotes lymphatic metastasis and epithelial-mesenchymal transition (EMT) of head and neck squamous carcinoma cells by stabilizing slug mRNA in an m 6 A-dependent manner 168 . In addition, human papillomavirus E6/E7 promotes aerobic glycolysis of cervical cancer by stabilizing MYC expression in IGF2BP2-mediated m 6 A-dependent way 169 . In breast cancer stem-like cells (BCSC), aurora kinase A (AURKA) binds to IGF2BP2 and strengthens IGF2BP2 to stabilize DROSHA mRNA in an m 6 A-modified way, thereby increasing BCSC stemness maintenance 170 .…”
Section: The Role Of Igf2bps As M 6 a Reader In Ca...mentioning
confidence: 99%
“…IGF2BP2 also promotes lymphatic metastasis and epithelial-mesenchymal transition (EMT) of head and neck squamous carcinoma cells by stabilizing slug mRNA in an m 6 A-dependent manner 168 . In addition, human papillomavirus E6/E7 promotes aerobic glycolysis of cervical cancer by stabilizing MYC expression in IGF2BP2-mediated m 6 A-dependent way 169 . In breast cancer stem-like cells (BCSC), aurora kinase A (AURKA) binds to IGF2BP2 and strengthens IGF2BP2 to stabilize DROSHA mRNA in an m 6 A-modified way, thereby increasing BCSC stemness maintenance 170 .…”
Section: The Role Of Igf2bps As M 6 a Reader In Ca...mentioning
confidence: 99%
“…The m6A regulators regulated the m6A methylation in MYC, affecting the stability and translation efficiency of MYC, and then regulated the expression of MYC, which was an important mechanism for the occurrence and development of cancers ( Wu et al, 2021 ; Zheng et al, 2022 ). The m6A regulators of METTL3/5, FTO, IGF2BP1/2/3, YTHDF2 ( Einstein et al, 2021 ; Iaiza et al, 2021 ; Yang et al, 2021 ; Chen et al, 2022 ; Du et al, 2022 ; Hu et al, 2022 ; Huang et al, 2022 ; Liu et al, 2022 ; Luo and Lin, 2022 ), and so on had been proven to modulate the mechanism. In our study, compared with the healthy control, MYC mRNA levels were lower in both NAFL and NASH, while no differences were found between NAFL and NASH.…”
Section: Discussionmentioning
confidence: 99%
“…The studies have shown that the oncogenic potential of high-risk HPV 16 genotypes is determined by the E6 and E7 oncogenes. These two viral oncogenes are often co-expressed in cervical cancer cells and regulate the occurrence and maintenance of cervical cancer ( Hu et al, 2022 ). Their open reading frames are directly involved in regulating the growth of cervical cancer cells, play a key role in the proliferation of cervical cancer cells, and are closely related to the apoptosis of cervical cancer cells ( Wen et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%